INTERPRETABLE MACHINE LEARNING DENGAN PENDEKATAN MODEL AGNOSTIK PADA PREDIKSI FUEL CONSUMPTION RATE MINING HAUL TRUCK - Domy Guruh Dwi Arbianto; Jerry Dwi Trijoyo Purnomo (Smart Education, 2026)
Abstract: Machine learning (ML) models are frequently characterized as